Fever Narrative in the Fiction of Charles Dickens - Smith, Ralph (Université d'Ottawa / University of Ottawa, 2012)
This thesis argues that what it terms fever narratives figure prominently in Charles Dickens’s fiction. Fever was regarded not as a symptom but as a generic disease that had sub-species, such as cholera, smallpox, typhus and typhoid, and that presented itself through devastating epidemics that frightened the public and drove the government to enact public health legislation. The core elements of the fever narrative – such as fever’s cause, pathology, treatment and prevention – were still not clearly understood. This inevitably heightened public anxiety and frustration, particularly given lengthy delays in the bureaucratic processes of Parliament and local governments in dealing with fever’s perennial threat. The politically favoured sanitarian narrative influenced Dickens significantly. Sanitarians believed that water and sewer projects in urban localities and improved sanitary practices would prevent most diseases. However, Dickens was influenced also by an alternative approach that this thesis calls the “medical narrative,” comprising a more holistic vision of public health, reliant on improved treatments, greater medical professionalism, and specialized hospitals, in addition to sanitary reform. Dickens’s 1840s novels reflected both approaches, but he emphasized the medical narrative in portrayals of the fevers of individual characters. In the 1850s, the predominant focus of fever narratives in Dickens’s journals and novels became fever of the social body – fever that figuratively infected English institutions or the country as a whole. Dickens’s fever narratives became progressively darker during these two decades and, with each novel onward from Dombey and Son (1846-48), his representations of fever apocalypses infecting both the rich and the poor became more strident, even to the extent of suggesting that the whole institutional and economic infrastructure of the country would suffer an irrevocable blow. The thesis argues that Dickens presented these minatory scenes of vengeance in response to what he perceived as the blindness of the middle class to the condition of the sick and poor of England. This reached a climax with “Revolutionary fever” in A Tale of Two Cities (1859). The thesis presents a final argument that Dickens’s stories of the early 1860s and Our Mutual Friend (1864-65) provided both a continuation of and a denouement for the two previous decades’ fever narratives, by offering a view of the dust of corpse upon corpse of those who were mowed down by fever, and of a river polluted by this dust. However, he foresees also the possibility of the fundamental regeneration of a more humane physical, social and institutional environment in England.
Keywords: Dickens; sanitary reform; nineteenth-century public health; narrative